Estudo toponímico: uma análise acerca dos topônimos de origem indígena identificados no município de Inhangapi-PA - FERREIRA, Rafaela Carla de Souza (2020)
This work present a research about the toponymy, a subject-matter of the linguistic area that has as object of study the Toponyms, meaning the names designations for a place or geographies accidents. In this way, the work has as objective to analyze and to reflect about of the Toponyms from indigenous people (Tupi) which give names for places such as communities, extensions, farms and igarapés of the municipality of Inhangapi-PA, located in the mesoregion northeast of Pará. We intend, from there, to describe the etymology of toponyms, from the etymological dictionaries of Bueno (1998), Sampaio (1987), Tibiriçá (1984, 1985) end Cunha (1998); to analyze your morphological structure, identifying them as simple, simple hybrid, compound end compound hybrid; ascertain the changes morphologic end phonetic of designative; and classify them according to the taxonomic model developed by Dick (1990). The Methodology used the following steps: bibliographic survey, collect, selection and analysis of data, which were taken out from the map of the municipality provided by the Brazilian Institute of Geography and Statistics - IBGE. For the concretiztion of this work, we rely on the theoretical and methodological assumptions developed by Dick (1990), as well as other authors who have also developed their studies in the area of Toponymy, such as Carvalhinhos (2003, 2008), Carvalho (2003, 2010), Isquerdo (2008) and Andrade (2006, 2010). The results obtained in this analysis show that, when dealing with the morphological structure, most toponyms present a simple structure. Regarding the taxonomic classification, the predominance of the Taxi Phytotoponym, which includes the toponyms of vegetal provenance, was evidenced. Thereby, we verified that the characteristics referring to the flora were the motivational causes that most influenced the denominator in the process of naming the localities which are part of the municipality in focus.